Left–right patterning in congenital heart disease beyond heterotaxy. Issue 1 (30th January 2020) - Gabriel, George C.; Lo, Cecilia W.
Abstract: Congenital heart defect is one of the most common structural birth defects in the human population. It is highly associated with heterotaxy, a birth defect involving randomized left–right patterning of visceral organ situs. Large scale mouse forward genetics have led to the finding of a central role for cilia in CHD pathogenesis, with some cilia and non‐cilia mutations causing CHD with heterotaxy. Interestingly, many of the mutations causing CHD with heterotaxy can give rise to three laterality outcomes comprising normal situs solitus, mirror symmetric situs inversus totalis, or randomized situs with heterotaxy. Given CHD is largely observed only with heterotaxy, this suggests a new paradigm is needed for investigating the genetics of CHD associated with heterotaxy. Furthermore, analysis of data from multiple large birth cohorts have independently confirmed a broader involvement of laterality disturbance in CHD. This was demonstrated by the common cooccurrence of rare laterality defects with CHD lesions of a wide spectrum. These findings suggest left–right patterning is tightly intertwined with the developmental processes that regulate cardiac morphogenesis and its disturbance may contribute to all types of CHD even in the absence of laterality defects.